Impostor syndrome : a novel - Wang, Kathy (Custom House, 2021)
"From the critically acclaimed author of Family Trust comes a new satire, exploring the fiercely competitive world of women in Silicon Valley in a thrilling tale of foreign espionage and personal secrets"--